The Active Components of Sunflower (Helianthus annuus L.) Calathide and the Effects on Urate Nephropathy Based on COX-2/PGE2 Signaling Pathway and the Urate Transporter URAT1, ABCG2, and GLUT9 - Dai, Huining; Lv, Shuai; Qiao, Zi'an; Wang, Kaiyu; Zhou, Xipeng; Bao, Chunyang; Zhang, Shitao; Fu, Xueqi; Li, Wannan (Frontiers in Nutrition, 2022)
The sunflower (Helianthus annuus L.) calathide is gradually used as an alternative treatment for hyperuricemia; nevertheless, evidence regarding its main components and therapeutic capacity for urate nephropathy is lacking. Identification of sunflower calathide aqueous extract (SCE) was rapidly done by UPLC-ESI-Q-Orbitrap, and 32 water-soluble compounds with a comprehensive score >80 were discovered. Besides, yeast extract was administrated to induce high UA levels and hyperuricemic renal injury. We found that SCE treatment not only decreased UA levels to a comparable degree as allopurinol and benzbromarone, but also reduced the BUN levels and participated in kidney injury repair induced by uric acid. Moreover, it regulated the expression of URAT1 and ABCG2, especially inhibiting the GLUT9 in the normal kidney. Results were multifacetedly evaluated with a view to suggesting a possible mechanism of action as compared with those of allopurinol and benzbromarone by western blotting, H&E staining, and immunohistochemistry. However, the H&E staining showed histological changes in model, benzbromarone, and allopurinol groups rather than SCE treatments, and at the same time, the uric acid was identified as a cause of renal damage. The antiinflammatory effects and the regulations of COX-2/PGE2 signaling pathway were revealed on the LPS-induced RAW264.7 cells, indicating that the SCE not only increased cellular proliferation but also downregulated the COX-2, PGE2, NO, and IFN-γ cytokines in the RAW264.7 cells. To conclude, the SCE acts on urate transporters and contributes to prevent urate nephropathy via alleviating inflammatory process involving COX-2/PGE2 signaling pathway. It is available to develop SCE as food supplemental applications for hyperuricemia and nephritic inflammation.